Atrial Fibrillation, Neurocognitive Decline and Gene Expression After Cardiopulmonary Bypass - Rahul S. Dalal (Revista Brasileira de Cirurgia Cardiovascular/Brazilian Journal of Cardiovascular Surgery, 2015)
Objective: Atrial fibrillation and neurocognitive declineare common complications after cardiopulmonary bypass. Byutilizing genomic microarrays we investigate whether geneexpression is associated with postoperative atrial fibrillationand neurocognitive decline.Methods: Twenty one cardiac surgery patients were prospectivelymatched and underwent neurocognitive assessments pre-operatively and four days postoperatively. The whole bloodcollected in the pre-cardiopulmonary bypass, 6 hours after-cardiopulmonary bypass, and on the 4thpostoperative day washybridized to Affymetrix Gene Chip U133 Plus 2.0 Microarrays.Gene expression in patients who developed postoperative atrialfibrillation and neurocognitive decline (n=6; POAF+NCD) wascompared with gene expression in patients with postoperativeatrial fibrillation and normal cognitive function (n=5; POAF+NORM)and patients with sinus rhythm and normal cognitive function(n=10; SR+NORM). Regulated genes were identified using JMPGenomics 4.0 with a false discovery rate of 0.05 and fold changeof >1.5 or <-1.5.Results: Eleven patients developed postoperative atrialfibrillation. Six of these also developed neurocognitive decline.Of the 12 patients with sinus rhythm, only 2 developedneurocognitive decline. POAF+NCD patients had unique regulationof 17 named genes preoperatively, 60 named genes six hoursafter cardiopulmonary bypass, and 34 named genes four dayspostoperatively (P<0.05) compared with normal patients. Pathwayanalysis demonstrated that these genes are involved in cell death,inflammation, cardiac remodeling and nervous system function.Conclusion: Patients who developed postoperative atrialfibrillation and neurocognitive decline after cardiopulmonarybypass may have differential genomic responses compared tonormal patients and patients with only postoperative atrialfibrillation, suggesting common pathophysiology for theseconditions. Further exploration of these genes may provideinsight into the etiology and improvements of these morbidoutcomes.